Exploring Traffic Flows in the Online News Media Ecosystem - Spyridou, Lia Paschalia; Manavopoulos, Vasilis (My University, 2021)
For more than two decades the news industry is faced with instability and confusion. Within a fluid and hyper-competitive news media ecosystem (Anderson, Bell & Shirky, 2012) news organizations face dwindling revenue and declining journalistic authority -in terms of both trust and impact (Nielsen & Selva, 2019). Significant worries about the future of journalism are often mitigated by the proliferation of (non-profit) web natives which experiment with forms of civic journalism (Harlow & Salaverría, 2016; Nelson, 2019). On the other hand, research suggests that news consumption patterns reveal legacy-related benefits for well-established outlets (Arrese & Kaufmann, 2016), while algorithmic recommendations by the platforms tend to decrease diversity to news exposure (Carlson, 2017; Diakopoulos, Trielli, Stark & Mussenden, 2018). Employing data from similarWeb (similarWeb.com), we investigate the flow of user internet traffic related to the Greek news organisations ecosystem between March – May 2019. Using the top 100 news sites by traffic as the unit of analysis, we attempt to map the relative size of attention different types of news organisations attract, as measured by clicks. Subsequently, treating the various websites as nodes forming a network, we employ Social Network Analysis to explore the connections, in terms of traffic flow exchanges, between the various sites, as well as the flows from outside toward the media ecosystem (e.g. through direct traffic, searches, social media etc.). The study contributes to the broader discussion on evolving attention patterns of news consumption and power balances between media outlets as well as between platforms and news companies.